2020
DOI: 10.1017/s0967199420000398
|View full text |Cite
|
Sign up to set email alerts
|

Porcine follicular fluid derived from > 8 mm sized follicles improves oocyte maturation and embryo development duringin vitromaturation of pigs

Abstract: Summary The aim of the present study was to investigate the effects of porcine follicular fluid (pFF) from large-sized (LFF; >8 mm in diameter) and medium-sized (MFF; 3–6 mm in diameter) follicles on the maturation and developmental competence of porcine oocytes. Cumulus–oocyte complexes (COCs) were collected from follicles 3–6 mm in diameter. The collected COCs were incubated for 22 h with LFF or MFF (in vitro maturation (IVM)-I stage) and were incubated subsequently for 22 h with LFF or MFF (IVM-II sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Previous reports indicate that addition of PFF to IVM medium effectively inhibits polyspermy after IVF [ 32 ] and contributes to improving the normal monospermic fertilization [ 33 ]. In another study, oocytes matured in a medium containing PFF showed enhanced embryonic development [ 34 ]. Generally, PFF is aspirated from the antral follicles, and the composition of PFF differs depending on the size of follicles [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicate that addition of PFF to IVM medium effectively inhibits polyspermy after IVF [ 32 ] and contributes to improving the normal monospermic fertilization [ 33 ]. In another study, oocytes matured in a medium containing PFF showed enhanced embryonic development [ 34 ]. Generally, PFF is aspirated from the antral follicles, and the composition of PFF differs depending on the size of follicles [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate effect of ALA on cumulus expansion, twenty to thirty COCs in each group were used to assess cumulus expansion at 22 h after IVM. Image J software (version 1.46; National Institutes of Health, Bethesda, MD, USA) was used to measure the area of each COCs, and all of cumulus expansion data were normalized to non-ALA group at 0 h (Park et al, 2020). Fulka, 1976;Park et al, 2020).…”
Section: Assessment Of Cumulus Expansionmentioning
confidence: 99%
“…The cumulus cells were denuded by gently pipetting in maturation medium containing 0.1% (w/v) hyaluronidase and denuded oocytes were fixed in 4% (v/v) paraformaldehyde solution at room temperature for 7 min. Then, they were stained with 5 μM CellTracker TM for 30 min in a dark room (Park et al, 2020). Stained oocytes were washed three times with PBS-PVA and were observed under an epifluorescence microscope with optical filter (ex: 510-560 nm, em: 590 nm).…”
Section: Measurement Of Intracellular Gsh Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological maturity of the preovulatory follicle, indicating its readiness nurture the maturing oocyte, is positively associated with circulating estradiol concentration and follicle size ( 11 ). In cattle ( 11–13 ), humans ( 14 ), and swine ( 15 , 16 ) the maturity of the preovulatory follicle at the time of a gonadotropin releasing hormone (GnRH)-induced LH surge affects establishment and maintenance of pregnancy. Increased preovulatory follicle diameter and higher levels of circulating estradiol at GnRH administration were associated with improved embryo quality and increased overall embryo cleavage and blastocyst development rates ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%